Effect of Magnetic Field on Plasma Zn, Cu and Malondialdehyde Levels and Na+-K+ Atpase Activity of Isolated Diaphragmatic Muscle in a Diabetic Rat Model - DEMIRKAZIK*, A.; YUCEBILGIC†, G.; EMRE‡, M.; PELIT‡, A.; CETIN§, A.; GULTURK¶, S.; KAVAK#, S. (Asian Journal of Chemistry, 2009)
The aim of this study is to investigate the effect of magnetic field (MF) on plasma Zn, Cu and malondialdehyde (MDA) levels and Na+-K+ ATPase activity of isolated diaphragmatic muscle in a diabetic rat model. Rats allocated as control (n = 10), diabetes mellitus (DM) (n = 10), MFexposed (MFE) (n = 10) and DM plus MF-exposed (DM-MFE) (n = 10) groups. After induced DM, the MF were exposed to MF in solenoid 165 minutes every day during 1 month. Cardiac blood was obtained and the plasma Zn, Cu and MDA levels and Na+- K+ ATPase activity of diaphragmatic muscle were determined. Plasma Cu level of the control was significantly lower than those of the DM and MFE (p < 0.05). Plasma Zn level of the DM-MFE was significantly lower than those of the control, DM and MFE (p < 0.05). Plasma MDA level of the DM was significantly higher than those of the control, MFE and DM-MFE (p < 0.05). Diabetes mellitus and magnetic field increase plasma Cu level and do not affect plasma Zn level, but MF plus DM decreases its level. While DM increases plasma MDA level, MF has opposing effect on MDA level. Diabetes mellitus decreases Na-K ATPase of rat diaphragmatic muscle and MF elevates its level to normal.